Strain rate effect and micro-buckling behavior of anisotropy macromolecular separator for lithium-ion battery - W. Q. Hao; J. M. Xie; X. Zhang; P. Wang; F. H. Wang (eXPRESS Polymer Letters)
High tensile strength and good toughness play an important role in improving the mechanical performance of separator films, such as resistance to external force, service life and so on. In the present research, the strain rate effect and microbuckling behavior of two types of anisotropic separators for lithium-ion battery (LIB) under different strain rates are investigated. The results conclude that the anisotropy effect and strain rate effect are displayed obviously along the machine direction (MD), diagonal direction (DD) and transverse direction (TD). The constitutive relationship with a strain rate of anisotropicmacromolecular separator for LIB is ln{ε/σ-1/(E0[1+λ1(lnε.-lnε.0)])}=κlnε-lnE0-ln[1+λ1(lnε.-lnε.0)]. The separator has high tensile strength along MD and good toughness along DD and TD. The maximum error of strain rate strengthening coefficient λ1 and λ/ about the material parameter is less than 15%. Finally, the critical stress σx,crit = –Ekπ2(t/B)2/12(1 – μ2) characterizing the micro-buckling behavior of macromolecular separators are proposed and discussed. The critical stress error rates are approximately Error = 2–7% compared with experimental results. This research provides guidance to improve the mechanical property of anisotropic separator and addresses the safety of LIB.